Alaska Open-file Report 144 Assessment of Thermal Springs Sites Aleutian Arc, Atka Island to Becherof Lake -- Preliminary Results and Evaluation - Motyka, R. J.; Moorman, M. A.; Liss, S. A. (State of Alaska Department of Natural Resources, 1981)
Twenty of more than 30 thermal spring areas reported to exist in the Aleutian arc extending from Atka Island to Becherof Lake were investigated during July and August, 1980. Thermal activity of three of these sites had diminished substantially or no longer existed. At least seven more sites where thermal-spring activity is probable or certain were not visited because of their remoteness or because of time constraints. The existence of several other reported thermal spring sites could not be verified; these sites are considered questionable. On the basis of geothermometry, subsurface reservoir temperatures in excess of 150 C are estimated for 10 of the thermal spring sites investigated. These sites all occur in or near regions of Recent volcanism. Five of the sites are characterized by fumaroles and steaming ground, indicating the presence of at least a shallow vapor-dominated zone. Two, the Makushin Valley and Glacier Valley thermal areas, occur on the flanks of active Mukushin Volcano located on Unalaska Island, and may be connected to a common source of heat. Gas geothermometry suggests that the reservoir feeding the Kliuchef thermal field, located on the flanks of Kliuchef volcano of northeast Atka Island, may be as high as 239 C.